2019
DOI: 10.3390/antiox8120575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Stevioside Supplementation Alleviates Lipopolysaccharide-Induced Intestinal Mucosal Damage through Anti-Inflammatory and Antioxidant Effects in Broiler Chickens

Abstract: The study was conducted to investigate the effects of dietary stevioside (STE) supplementation on the lipopolysaccharide (LPS)-induced intestinal mucosal damage of broiler chickens. A total of 192 one-day-old male Ross 308 broiler chicks were randomly divided into four treatments: (1) basal diet (CON); (2) basal diet supplemented with 250 mg/kg stevioside (STE);(3) basal diet + LPS-challenge (LPS); (4) basal diet supplemented with 250 mg/kg stevioside + LPS-challenge (LPS + STE). LPS-challenged groups received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 62 publications
(89 reference statements)
5
52
0
Order By: Relevance
“…The results suggested that those 3 sweeteners did not induce oxidative stress in the jejunal mucosae. Nevertheless, our recent study has demonstrated that dietary supplementation with STE is able to alleviate lipopolysaccharide-induced intestinal mucosal damage through antioxidant and anti-inflammatory effects in broiler chickens ( Jiang et al., 2019b ). In agreement, STE could also enhance the antioxidant capacity of jejunal mucosae in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that those 3 sweeteners did not induce oxidative stress in the jejunal mucosae. Nevertheless, our recent study has demonstrated that dietary supplementation with STE is able to alleviate lipopolysaccharide-induced intestinal mucosal damage through antioxidant and anti-inflammatory effects in broiler chickens ( Jiang et al., 2019b ). In agreement, STE could also enhance the antioxidant capacity of jejunal mucosae in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 treatments were as follows: (1) broiler chickens fed a basal diet ( CON ); (2) broiler chickens fed a basal diet supplemented with 250 mg/kg STE; (3) broiler chickens fed a basal diet supplemented with 100 mg/kg SUC; (4) broiler chickens fed a basal diet supplemented with 600 mg/kg SAC. The supplemental level of STE was chosen according to our previous study ( Jiang et al., 2019b ). The supplemental levels of SUC and SAC were chosen according to a previous study to obtain equivalent sweetness with the amount of STE ( Keast et al., 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…Maintaining intestinal health and the integrity of intestinal barrier function is essential for the growth and wellbeing of animals. Several pathogenic factors such as stress and pathogenic bacteria challenges can cause inflammation and damage to the intestinal barrier 67 . On day 14 post P. multocida challenge, greater effects were found for probiotic supplementation on HIF1A, and TSG-6 (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic index was calculated as the percentage of cells that tested TUNEL-positive with the Colorimetric TUNEL Apoptosis Assay Kit to follow our previous laboratory work [35]. The paraffin portion of the experiment was initially deparafinized, rehydrated, and then incubated for 20 min at room temperature with Proteinase K (20 g/mL).…”
Section: Tunel Stainingmentioning
confidence: 99%